2014
DOI: 10.1542/peds.2013-2880
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Phenotype of Scabies by Age

Abstract: WHAT'S KNOWN ON THIS SUBJECT:Scabies is a frequent cause of consultation and has recently been classified as a neglected disease. The clinical presentation seems to be linked with age, although no specific study has aimed to delineate the clinical spectrum of scabies in infants and children.WHAT THIS STUDY ADDS: Scabies in infants and children has distinct clinical features. This prospective observational study found that infants were more likely to have relapse, nodules, and to present involvement with extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
64
1
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 22 publications
11
64
1
10
Order By: Relevance
“…Nem sempre são evidentes, podendo estar mascarados pela escoriação, eczematização ou infeção secundária. 1,2,5,12,16 Os locais de eleição das lesões de escabiose são as pregas interdigitais das mãos e as faces laterais dos dedos das mãos, faces flexoras dos punhos ( Fig. 1), axilas, cotovelos, umbigo, cintura pélvica, tornozelos, pés e nádegas.…”
Section: 2518unclassified
See 3 more Smart Citations
“…Nem sempre são evidentes, podendo estar mascarados pela escoriação, eczematização ou infeção secundária. 1,2,5,12,16 Os locais de eleição das lesões de escabiose são as pregas interdigitais das mãos e as faces laterais dos dedos das mãos, faces flexoras dos punhos ( Fig. 1), axilas, cotovelos, umbigo, cintura pélvica, tornozelos, pés e nádegas.…”
Section: 2518unclassified
“…2,22 Num estudo prospetivo, que incluiu 323 crianças, verificou-se que o grupo de crianças com idade inferior a 2 anos apresentava como características distintivas um atingimento preferencial da cabeça, plantas e dorso dos pés, bem como a existência de familiares com prurido. 12 As recidivas foram mais frequentes em idades inferiores a 15 anos.…”
Section: 2518unclassified
See 2 more Smart Citations
“…Recent research found that involvement of the scalp and plantar surfaces of the feet were seen exclusively in patients less than two years old, and facial involvement was similarly unique to those under 15 (Boralevi et al 2014). Infants and young children may therefore present with both atypical distribution of lesions and non-specific symptoms such as poor feeding, disturbed sleep pattern and apparent distress (Johnston and Sladden 2005).…”
Section: Clinical Presentationmentioning
confidence: 99%